Fontan Fenestration Closure Prior to Posterior Spinal Fusion in Patients With Single-Ventricle Heart Disease. Issue 23 (1st December 2016) - Schwartz, Matthew C.; Nykanen, David; Fleishman, Craig; Munro, Hamish M.; Phillips, Jonathan; Knapp, Raymond D.; Felix, Donald
Abstract : Study Design: Case series. Objective: To describe transcatheter closure of the Fontan fenestration prior to posterior spinal fusion in two children to prevent paradoxical venous air embolism during the operation. Summary of Background Data: Scoliosis is common among patients with single-ventricle congenital heart disease who have undergone Fontan operation and spinal surgery can offer physiologic benefits. Venous air embolism is a rare, but important reported complication during spinal surgery performed in the prone position. Patients with Fontan circulation can have significant right to left shunting via a patent Fontan fenestration that can increase the risk of paradoxical systemic embolization of any entrained venous air. Methods: We retrospectively reviewed the charts of two patients with single-ventricle congenital heart disease who had undergone fenestrated Fontan operation and underwent transcatheter fenestration closure prior to spinal fusion. Results: Two patients with Fontan circulation underwent successful transcatheter fenestration closure with Amplatzer Ductal Occluder II devices. Five to 6 months after closure, both underwent uncomplicated posterior spinal fusion. Conclusion: Transcatheter closure of the Fontan fenestration prior to spinal fusion in two with Fontan circulation and scoliosis is a rare, but important indication for fenestration closure that warrants emphasis. Level of Evidence: N/A